Instigators of COVID-19 in Immune Cells Are Increased in Tobacco Cigarette Smokers and Electronic Cigarette Vapers Compared With Nonsmokers. Issue 3 (19th August 2021) - Kelesidis, Theodoros; Zhang, Yuyan; Tran, Elizabeth; Sosa, Grace; Middlekauff, Holly R
Abstract: Introduction: The severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2), the virus responsible for the COVID-19 pandemic, gains entry into the host cell when its Spike protein is cleaved by host proteases TMPRSS2 and furin, thereby markedly increasing viral affinity for its receptor, angiotensin-converting enzyme-2 (ACE2). In rodent and diseased human lungs, tobacco cigarette (TCIG) smoke increases ACE2, but the effect of electronic cigarette vaping (ECIG) is unknown. It is unknown whether nicotine (in both TCIGs and ECIGs) or non-nicotine constituents unique to TCIG smoke increase expression of key proteins in COVID-19 pathogenesis. Methods: Immune (CD45 + ) cells collected before the pandemic in otherwise healthy young people, including TCIG smokers ( n = 9), ECIG vapers ( n = 12), or nonsmokers (NS) ( n = 12), were studied. Using flow cytometry, expression of key proteins in COVID-19 pathogenesis were compared among these groups. Results: TCIG smokers and ECIG vapers had similar smoking or vaping burdens as indicated by similar plasma cotinine levels. TCIG smokers compared with NS had a significantly increased percentage of cells that were positive for ACE2 (10-fold, p < .001), TMPRSS2 (5-fold, p < .001), and ADAM17 (2.5-fold, p < .001). Additionally, the mean fluorescence intensity (MFI) consistently showed greater mean ACE2 (2.2-fold, p < .001), TMPRSS2 (1.5-fold, p < .001), furin (1.1-fold, p < .05), and ADAM17 (2-fold, p < .001) in TCIG smokers compared with NS. In ECIG vapers, furin MFI was increased (1.15-fold, p < .05) and TMPRSS2 MFI tended to be increased (1.1-fold, p = .077) compared with NS. Conclusions: The finding that key instigators of COVID-19 infection are lower in ECIG vapers compared with TCIG smokers is intriguing and warrants additional investigation to determine if switching to ECIGs is an effective harm reduction strategy. However, the trend toward increased proteases in ECIG vapers remains concerning. Implications: (1) This is the first human study to report a marked increase in proteins critical for COVID-19 infection, including ACE2, TMPRSS2, and ADAM17, in immune cells from healthy tobacco cigarette smokers without lung disease compared with e-cigarette vapers and nonsmokers. (2) These findings warrant additional investigation to determine whether switching to electronic cigarettes may be an effective harm reduction strategy in smokers addicted to nicotine who are unable or unwilling to quit. (3) The increase in proteases in electronic cigarette vapers remains concerning.